[en] NEW DEMANDS FOR OLD QUESTIONS: PROFESSIONAL REQUESTS TO SOCIAL WORKERS IN PHILANTHROPIC INSTITUTIONS AFTER SUAS - PRISCILA AMBROZIO GONÇALVES (MAXWELL, 2018)
[pt] A presente dissertação Novas demandas para velhas questões: requisições profissionais aos assistentes sociais em instituições filantrópicas pós SUAS teve como principal objetivo analisar as requisições das entidades filantrópicas ao trabalho do Assistente Social após a implementação do Sistema Único de Assistência Social (SUAS), a partir de 2005. O estudo realizou uma análise crítica do processo de implementação do SUAS e as novas regulações para o trabalho das entidades filantrópicas que este sistema de gestão tem desenvolvido ao longo de sua institucionalização no Brasil, que está permeado por disputas e contradições, entre práticas tradicionais e conservadoras e, por outro lado, que buscam a profissionalização desses serviços, historicamente vinculados à caridade e à benesse. Verifica-se que estas regulações incorporam a lógica gerencialista e burocratizante da reforma das políticas sociais, iniciada no Brasil, na década de 1990, com o apelo neoliberal e que impactam diretamente nas requisições aos profissionais que atuam nestes espaços, em particular os assistentes sociais. === [en] The present dissertation New demands for old questions: professional requests to social workers in philanthropic institutions after SUAS, had as main objective to analyze the requisitions of the philanthropic entities to the work of the Social Worker after the implementation of the Unique System of Social Assistance (SUAS), from 2005. carried out a critical analysis of the process of implementation of SUAS and the new regulations for the work of the philanthropic entities that this management system has developed throughout its institutionalization in Brazil that is permeated by disputes and contradictions between traditional and conservative practices and, on the other hand, that seek the professionalization of these services, historically linked to charity and benesse. It is verified that these regulations incorporate the managerialist and bureaucratic logic of the social policies reform, initiated in Brazil in the 1990s with the neoliberal appeal and that directly impact the requisitions to the professionals that work in these spaces, in particular the social workers.